PHASE RELATIONS AND DIAMOND SYNTHESIS IN THE CARBONATE-SILICATE ROCKS OF THE CHAGATAI COMPLEX, WESTERN UZBEKISTAN: RESULTS OF EXPERIMENTS AT P = 4-7 GPA AND T = 1200-1700°C - Bobrov A.V.; Litvin Yu.A.; Divaev F.K. (My University, 2004)
This paper presents the results of an experimental study of phase relations in a carbonate-silicate system at 4.0-7.0 GPa and 1200-1700°C for two natural samples of melanocratic carbonate-silicate rocks of the Chagatai Complex, where diamond crystals have been discovered. The experimental investigations allowed us to simulate the initial (mantle) silicate association of the carbonate-silicate rocks of the Chagatai Complex. This association is similar to high-Ca eclogite and grospidite from kimberlite pipes, which provides an explanation for the occurrence of diamond in these rocks. The high solubility of silicate material in a carbonate medium at high P-T parameters was qualitatively demonstrated. Based on the experimental results, a scheme of phase relations was constructed for the carbonate-silicate system at 7 GPa and 1200-1700°C. which reflects some features of carbonate-silicate magma solidification under mantle conditions depending on its composition. We established experimentally for the first time that melts of natural diamondiferous carbonatites, over-saturated with respect to dissolved carbon, are highly efficient diamond-forming media under the thermodynamic conditions of diamond stability.